2015
DOI: 10.1021/acs.nanolett.5b01581
|View full text |Cite
|
Sign up to set email alerts
|

IR-Driven Photocatalytic Water Splitting with WO2–NaxWO3 Hybrid Conductor Material

Abstract: An IR-driven photocatalytic water splitting system based on WO2-NaxWO3 (x > 0.25) hybrid conductor materials was established for the first time; this system can be directly applied in seawater. The WO2-NaxWO3 (x > 0.25) hybrid conductor material was readily prepared by a high-temperature reduction process of semiconductor NaxWO3 (x < 0.25) nanowire bundles. A novel ladder-type carrier transfer process is suggested for the established IR-driven photocatalytic water splitting system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 47 publications
4
59
0
Order By: Relevance
“…Recently, Tang et al. reported a novel material composed of WO 2 –Na x WO 3 ( x >0.25) hybrid conductor materials for IR‐light water splitting . In addition to the tungsten conductive oxides, other hybrid conductive oxides MO 2 –A x MO 3 (M=V, Mo, Ta, Re, Nb, Tc, Ru; A=Na, K, Sr; x = not defined) are proposed to potentially have similar photocatalytic properties.…”
Section: Mechanismsmentioning
confidence: 99%
“…Recently, Tang et al. reported a novel material composed of WO 2 –Na x WO 3 ( x >0.25) hybrid conductor materials for IR‐light water splitting . In addition to the tungsten conductive oxides, other hybrid conductive oxides MO 2 –A x MO 3 (M=V, Mo, Ta, Re, Nb, Tc, Ru; A=Na, K, Sr; x = not defined) are proposed to potentially have similar photocatalytic properties.…”
Section: Mechanismsmentioning
confidence: 99%
“…This allows for a controlled plasmon tuning over a wide spectral range via chemical treatment, either during synthesis [1,8,26] or post-synthesis, [11][12][13]22] making these materials very appealing for numerous applications. [10,[27][28][29][30][31][32][33] In vacancy doped semiconductors and in particular in copper chalcogenides, plasmon tuning goes in hand with redox-chemical reactions and a simultaneous removal/insertion of copper, as well as structural changes of the crystal lattice. [11][12][13] In metal oxide nanostructures instead the incor-poration of additional carriers can also be induced by capacitive charging.…”
Section: Introductionmentioning
confidence: 99%
“…The main effect responsible for the improved performance was related to plasmon induced hot electron injection from the ITO NCs to the single layer graphene in combination with the light confinement effect of the supporting Ge nanoneedle array [291]. The works highlighted above highlight the possibility to exploit the NIR LSPR for light harvesting upon plasmon induced hot carrier extraction in the NIR [33,271,292]. As also shown for example, in Cu 2-x S nanoplate/reduced graphene oxide electrodes serving as active electrocatalysts for the oxygen reduction reaction [143].…”
mentioning
confidence: 99%
“…Particularly,t he gapless energy-band structuresa nd high carrier mobility,m ake them potential materials for utilizationu nder IR light.R ecently,T ang et al reported an ovel materialc omposed of WO 2 -Na x WO 3 (x > 0.25) hybridc onductor materials for IR-lightw ater splitting. [73] In addition to the tungsten conductive oxides, other hybrid conductive oxidesM O 2 -A x MO 3 (M = V, Mo, Ta ,R e, Nb, Tc ,R u; A= Na, K, Sr; x = not defined) are proposed to potentially have similar photocatalytic properties.…”
Section: Metallic-oxide Conductor Materialsmentioning
confidence: 99%